Molecular Docking Study of Chemical Content of Ciplukan (Physalis angulata) As Antituberculosis and Prediction of Pharmacokinetic and Toxicity Parameters - Rahmawaty Hasan; Nur Diana Kholidah; Aqidatun Naffiah Choirunniza (Tinctura, 2025)
The existence of M. tuberculosis resistance to drugs caused by certain genetic mutations is a problem in the treatment of tuberculosis, so that necessary to develop new drugs. This study aims to analyze the interaction of the activity of potential compounds in ciplukan plants against the tuberculosis target protein, namely Anthranilate phosphoribosyl transferase (trpD) with PDB ID: 3R6C. The chemical content of ciplukan was selected through a preliminary study using webfrom superpred and way2drug, then docking was carried out using Autodock tools4.2 which has been validated and predicted pharmacokinetics and toxicity. The results of molecular docking showed the 3 best compounds, namely physanolideA, physagulinC, and physagulinH with bond energy values of -9.48, -9.27, and -9.13 kcal/mol. The compound shows pharmacokinetic predictions of having high absorption in the gastrointestinal tract, and does not inhibit enzymes that play a role in metabolizing drugs, and the physicochemical profile with inappropriate Lipinski criteria indicates that the compound is not suitable for oral drug preparation, so that expected that there will be structural modifications to improve the expected physicochemical properties. Prediction of toxicity in these compounds has high toxicity except phisagulinH whose toxicity can still be tolerated and can result in carcinogenicity except physanolideA compounds.